Education nation : six leading edges of innovation in our schools - Chen, Milton (San Francisco, CA. : Jossey-Bass, 2010)
'In Education Nation author Milton Chen draws from extensive experience in media--from his work on Sesame Street in its nascent years to his current role as executive director of the George Lucas Educational Foundation--to support his vision for a new world of learning. Presented in five parts and divided into'module' chapters, this book examines the ways in which K-12 learning can be revolutionized through innovative reform and the use of technology. Due in large part to new technologies, over the last few decades we've witnessed a huge shift in how we imagine teaching and learning. A good example is the educational revolution sparked by Sesame Street--which in its first season had a goal of teaching preschool-age children the numbers 1 to 10. At the time, experts dismissed it as an unrealistic goal since many kindergarten students were having trouble mastering this simple counting. Yet the research proved that preschool-age children learned those skills and many others directly from the TV screen. Now Sesame Street's curriculum teaches the numbers from 1 to 40. In today's digital age the number of new ways to teach and learn is ever-expanding and includes: television, Google, YouTube, TeacherTube, Facebook, iPhones, video games, GPS devices, open source textbooks, interactive whiteboards; and there are countless examples of ways technology positively impacts student learning--from voice-recognition software that helps children learn to read to translation tools that help teachers communicate with non-English speaking parents. As a result of constant innovation, learning is no longer limited by traditional confines and we're quickly moving beyond students tied to their chairs, desks, and textbooks--and teachers locked away in classrooms.'--
Record to be deleted.
Includes bibliographical references and index.
Keywords: School improvement programs -- United States; Educational innovations -- United States; Educational technology -- United States